Influence of tumor mutational burden, inflammatory gene expression profile, and PD-L1 expression on response to pembrolizumab in head and neck squamous cell carcinoma. Issue 2 (25th February 2022) - Haddad, Robert I; Seiwert, Tanguy Y; Chow, Laura Q M; Gupta, Shilpa; Weiss, Jared; Gluck, Iris; Eder, Joseph P; Burtness, Barbara; Tahara, Makoto; Keam, Bhumsuk; Kang, Hyunseok; Muro, Kei; et al.
Abstract : Background: To characterize genomic determinants of response to pembrolizumab in recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) in the KEYNOTE-012 study. Methods: Associations between biomarkers (tumor mutational burden (TMB), neoantigen load (NL), 18-gene T-cell-inflamed gene expression profile (Tcellinf GEP), and PD-L1 combined positive score (CPS)) and clinical outcomes with pembrolizumab were assessed in patients with R/M HNSCC (n=192). Tumor human papillomavirus (HPV) status was also evaluated with the use of p16 immunohistochemistry and whole exome sequencing (WES; HPV +, mapping >20 HPV reads) in pretreatment tumor samples (n=106). Results: TMB, clonality-weighted TMB, and Tcellinf GEP were significantly associated with objective response (p = 0.0276, p = 0.0201, and p = 0.006, respectively), and a positive trend was observed between NL and PD-L1 CPS and clinical response (p = 0.0550 and p = 0.0682, respectively). No correlation was observed between TMB and Tcellinf GEP (Spearman ρ=–0.026) or TMB and PD-L1 (Spearman ρ=0.009); a correlation was observed between Tcellinf GEP and PD-L1 (Spearman ρ=0.511). HPV status by WES and p16 immunohistochemistry showed concordance (84% ҡ=0.573) among patients whose HPV results were available using both methods. Conclusions: TMB and inflammatory biomarkers (Tcellinf GEP and PD-L1) may represent distinct and complementary biomarkers predicting response to anti-programmed death 1 therapies in HNSCC; further study of these relationships in randomized clinical trials is needed. Trial registration number: NCT01848834 .